Protocol for the Optimizing Naloxone Dispensing in Pharmacies (ONDP) Online Continuing Education Program: A Randomized Controlled Trial - Ashley Cid; Alec Patten; Michael Beazely; Kelly Grindrod; Jennifer Yessis; Feng Chang (Pharmacy, 2022)
The number of opioid-related deaths in Canada has steadily increased since 2016 and the COVID-19 pandemic has worsened this trend. Naloxone has been pivotal for reducing opioid-related harms and death, and pharmacists play a crucial role in ensuring the supply of naloxone to Canadians through community pharmacies. However, naloxone dispensing by pharmacists is not optimal; in fact, in Ontario, only 50% of pharmacists offer naloxone, despite national guidelines that pharmacists should offer naloxone to everyone with an opioid prescription. When asked why pharmacists do not proactively offer naloxone, recent research has identified that pharmacists need continuing education to boost confidence and knowledge on how to start conversations with patients. The study involves a delayed start, double-blind randomized controlled trial, for Canadian licensed pharmacists and pharmacy technicians. The goals of the program are to increase Canadian pharmacy professional’s knowledge, confidence, and motivation to proactively offer naloxone, as well as to decrease stigma associated with naloxone. The program incorporates behaviour change techniques from the Theoretical Domains Framework and the Theory of Planned Behaviour. The intervention program includes three modules that focus on improving pharmacists’ communication skills by teaching them how to proactively offer naloxone, while the control group will complete a reading assignment on the naloxone consensus guidelines. The program will involve a process and outcome evaluation in addition to a contribution analysis. This program is important for breaking down previously identified barriers and knowledge gaps for why pharmacists currently do not proactively offer naloxone. This study will provide important new information about what behaviour change techniques are successful in improving confidence and motivation in the pharmacy profession and in an online environment. Findings from this study can be used to produce a national naloxone education program that can also be implemented into current pharmacy school curriculum.